2020
DOI: 10.2217/pmt-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Lumbar Decompression: A Review of Indications, Techniques, Efficacy and Safety

Abstract: Lumbar spinal stenosis is a common degenerative spine condition. In properly selected patients, minimally invasive lumbar decompression ( mild®) may be an option to improve outcomes. This review provides an in-depth description of the mild procedure and a comprehensive examination of safety and efficacy. Two randomized controlled trials, together with 11 other controlled clinical studies, have established the efficacy of mild, which is a minimally invasive procedure that does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…These refractory patients represent a significantly different patient profile than those early in the continuum of care. 4 , 7 While the clinical superiority of mild to ESIs/CMM has been established by this and two other RCTs, 19 , 20 a suggested comparison of mild to open surgery presents several methodological challenges. First, these patient populations are at completely different phases on the treatment algorithm.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These refractory patients represent a significantly different patient profile than those early in the continuum of care. 4 , 7 While the clinical superiority of mild to ESIs/CMM has been established by this and two other RCTs, 19 , 20 a suggested comparison of mild to open surgery presents several methodological challenges. First, these patient populations are at completely different phases on the treatment algorithm.…”
Section: Discussionmentioning
confidence: 84%
“…This level of safety for the mild Procedure is supported by 13 clinical studies, including 2 Level 1 RCTs, that have demonstrated statistically significant efficacy improvement, superiority of mild versus ESIs, and low complication rates. 4 , 7 , 18–20 In fact, the safety of mild has been shown to be similar to ESIs at a 1.3% rate of device or procedure-related complications for both study groups in the ENCORE RCT. 19 It is important to note that all conservative and interventional therapies included in CMM in the MOTION study are positioned early in the treatment algorithm due to their low risk ( Table 4 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Published data suggest that this percutaneous direct decompression therapy has a high rate of success with limited risk. 3 For the Mild procedure, a five-point mean numeric pain-rating scale improvement 4 with mean ODI responder improvement of 32 points, 5 indicating significant pain reduction and functional improvement, has been achieved at 2-year follow-up. Historically, percutaneous direct decompression was performed by initially placing an epidural at the level or the level above the spinal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Although these data exist, patient selection for treatment candidacy and the procedure itself are evolving. 4 Percutaneous direct decompression procedurally has evolved from a dedicated ipsilateral incision and epidurogram to a midline incision with or without the need for an epidurogram. Although this has been employed in clinical practice, there has been no formal investigation of the safety of percutaneous direct decompression without the use of an epidurogram and relying on osteal landmarks.…”
Section: Introductionmentioning
confidence: 99%